2003
DOI: 10.1034/j.1600-0854.2003.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Golgi Matrix Distribution Exhibits the Same Dependence on Sar1p Activity as a Golgi Glycosyltransferase

Abstract: We investigated the relative distributional persistence of Golgi ‘matrix’ proteins and glycosyltransferases to an endoplasmic reticulum exit block induced by expression of a GDP‐restricted Sar1p. HeLa cells were microinjected with plasmid encoding the GDP‐restricted mutant (T39N) of Sar1p to block endoplasmic reticulum exit and then scored for the distribution of GM130 (Golgi matrix protein of 130 kDa), a cis located golgin; p27, a member of the p24 family of proteins; giantin, a protein that interacts indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 29 publications
6
46
0
Order By: Relevance
“…We also found that, although the addition of recombinant protein of Sar1T39N, which is a GDP-restricted mutant of Sar1 and had been used to block COPII-dependent trafficking (Zaal et al, 1999;Ward et al, 2001;Stroud et al, 2003), inhibited anterograde transport (supplementary material Fig. S6E, Sar1T39N), it did not affect the measurements that were obtained for retrograde transport (supplementary material Fig.…”
Section: Regulation Of Rab6 Recruitment To the Golgi Membranes By Yip1amentioning
confidence: 86%
“…We also found that, although the addition of recombinant protein of Sar1T39N, which is a GDP-restricted mutant of Sar1 and had been used to block COPII-dependent trafficking (Zaal et al, 1999;Ward et al, 2001;Stroud et al, 2003), inhibited anterograde transport (supplementary material Fig. S6E, Sar1T39N), it did not affect the measurements that were obtained for retrograde transport (supplementary material Fig.…”
Section: Regulation Of Rab6 Recruitment To the Golgi Membranes By Yip1amentioning
confidence: 86%
“…Storrie and colleagues (Miles et al, 2001) find that the distribution of golgins is sensitive to an ER exit block when higher concentrations of GTP-restricted Sar1p are used. Moreover, both Lippincott-Schwartz and colleagues (Ward et al, 2001) and Storrie and colleagues (Stroud et al, 2003) find that when GDP-restricted Sar1p is used to block ER exit, a condition that disrupts COPII stabilization of ER exit sites, that there is little, to no, difference in the response of Golgi matrix markers and Golgi enzymes. Both redistribute.…”
Section: Discussionmentioning
confidence: 99%
“…The exact point of transport block differs, however, depending on the particular mutated version being expressed. Expression of a GDP-restricted form of Sar1p, designated T39N, prevents the assembly of the COPII complex and this causes disassembly of the ER exit sites (Kuge et al, 1994;Stroud et al, 2003;Ward et al, 2001). By contrast, expression of a GTP-restricted form of Sar1p, designated H79G, inhibits export from the ER exit sites which otherwise assemble normally (Miles et al, 2001;Ward et al, 2001).…”
Section: Role Of Pka Activity In Golgi Biogenesismentioning
confidence: 99%